Urban poor and COVID-19 pandemic the historical legacies of the urban poor and the narratives of Brgy. 5-A, Bankerohan, Davao City amid a global health crisis - Nanlabi, Lei Nicole D. (2022)
This thesis study is an attempt to write the narratives of the urban poor communities in Barangay 5-A, Bankerohan, Davao City during the advent of the COVID-19 pandemic that is tied to the historical legacies of the urban poor in general. Likewise, part of the study was to answer the following questions of: (1) What are the challenges faced by the urban poor communities before and during the COVID-19 pandemic; (2) How do the urban poor cope with these challenges; and (3) How did the advent of COVID-19 influence and exacerbate their pre-existing challenges? To answer these questions, a qualitative phenomenological approach was used as the research design and interpretative phenomenological analysis (IPA) for the analysis of the data gathered through in-depth interviews. Six (6) self-reported urban poor respondents from Barangay 5-A were interviewed. The researcher has found out that ever since, the urban poor in Barangay 5-A had experienced a series of the following predicaments in: (1) housing and living environments; (2) livelihood and income source; and (3) digital preparedness. On the same note, these predicaments were also observed during the onset of the COVID-!9 pandemic but more highlighted. Because of these pre-existing predicaments, the findings revealed that the experiences of the urban poor communities are worse among others and that the pandemic policies do not consider the situation they are in. moreover, coping mechanisms of the urban poor were also explored: (1) involvement in low or unskilled jobs; (2) social networks; and (3) low cost necessities. With the advent of COVID-19 pandemic and its corresponding consequences, findings showed how difficult it was for the urban poor to keep these coping mechanisms. To conclude, urban poor communities have long been marked by poverty and many societal issues that have been exacerbated by the advent of COVID-19 pandemic. Moreover, with the formulation of new policies to mitigate the effects of this pandemic, it seems like the world has forgotten to consider the situation that the urban poor are in.